2019
DOI: 10.1002/advs.201802134
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment‐Triggered Aggregated Magnetic Nanoparticles for Reinforced Image‐Guided Immunogenic Chemotherapy

Abstract: Anticancer therapies, which can induce cell death and elevate antitumor immune response in the meantime, are considered as effective treatments for many types of cancers. Immunogenic cell death (ICD) induced by chemodrugs is a promising and typical strategy to achieve cell cytotoxicity and immunological enhancement together. However, due to the low level of ICD induction and less tumor‐targeting accumulation, application of traditional ICD inducers is limited. Here, tumor‐targeting core–shell magnetic nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 46 publications
0
69
0
Order By: Relevance
“…Most previous studies used solid iron‐based nanocrystals, such as iron oxide nanoparticles and FePt nanoparticles as the iron source to trigger Fenton chemistry in tumor . The amount of Fe 2+ /Fe 3+ ions released from these nanoparticles is influenced by pH value and reductive environment . Nevertheless, these solid nanocrystals show limited iron releasing efficiency.…”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…Most previous studies used solid iron‐based nanocrystals, such as iron oxide nanoparticles and FePt nanoparticles as the iron source to trigger Fenton chemistry in tumor . The amount of Fe 2+ /Fe 3+ ions released from these nanoparticles is influenced by pH value and reductive environment . Nevertheless, these solid nanocrystals show limited iron releasing efficiency.…”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…It has been reported that CDT and ferroptosis can elicit ICD by triggering dying tumor cells to generate damage-associated molecular patterns (DAMPs). [16] To study whether MnO x can elicit ICD, the crucial ICD biomarkers were detected. [17] Significant cell-surface calreticulin (CRT) exposure was observed in MnO x -treated group (Figure 2 a; Figure S28).…”
mentioning
confidence: 99%
“…DOX has been investigated for the ICD induction of tumor cells [ 45 ]. For example, chimeric polypeptide-conjugated DOX nanoparticles promoted IFN-γ secretion, facilitated the intratumoral infiltration of CD8 + T cells by ICD induction and more efficiently reduced tumor size than did DOX administered alone [ 46 ].…”
Section: Therapeutic Modalities That Induce Icdmentioning
confidence: 99%